An estimation of thermophilic Campylobacter population in ready-to-eat roast beef and chicken sold and hygiene practices of sellers in beer bars in Arusha, Tanzania. - Toyomaki, H.; Ishihara, K.; Sanka, P.; Kurwijila, Lusato R.; Grace, Delia; Makita, K. (2011)
Background: In Tanzania, ‘nyama-choma’ (roast beef) and ‘kuku-choma’ (roast chicken) are popular ready-to-eat foods served in beer bars. A separate risk assessment for thermophilic Campylobacter in Arusha showed that the incidence rate was 6.4 people (90% CI: 3.4-10.4) per 1000 peopleper day but the concentration of Campylobacter in beef, which was not studied, was the factor influencing the results of the assessment the most. The present study was thus conducted to understand the concentration of thermophilic Campylobacter on roast beef and chicken surfaces as well as that on raw beef using the most probable number (MPN) approach. Methods: A survey was conducted in Arusha, Tanzania in September and October 2010 and 30 samples of beef sold at butchers and 30 samples of roast beef and 10 samples of roast chicken sold at nyama-choma beer bars were collected and these butchers and bar owners were interviewed for the sales and hygiene information. Fifty grams of samples were rinsed with 25 ml of Phosphate Buffered Saline (PBS) and one ml of each three replicates of this solution and 10 and 100 times diluted solutions were inoculated to Preston broth and incubated at 42°C for 24 hours in a CO2 jar. The solutions were then cultured on CCDA agar at 42°C for 48 hours and the isolates were sub-cultured on blood agar and the DNA was extracted. The extracted DNA was tested for thermophilic Campylobacter using PCR and positive DNA was tested for both C. jejuni and C. coli. The MPN of the isolates was obtained from the MPN table. Results: Out of 70 samples, thermophilic Campylobacter isolates were detected from one sample of roast chicken and identified as C. coli. The prevalence was therefore 0% (0/30) for beef at butchers, 0% (0/30) for roast beef and 10% (1/10) for roast chicken. The MPN of the C. coli was 0.37/g of meat (95% CI: 0.07 – 1.0). A low recovery rate and the small value of MPN might be due to dry and hot selling environment in butchers and heat of roasted meats. According to the interviews with 30 butchers, 7 respondents (23%) had a refrigerator and 16 (53%) had received hygiene training. Similarly, out of 40 nyama-choma beer bar owners where 30 roast beef and 10 roast chicken were sampled, 8 (20%) had a refrigerator and 21 (53%) had been trained. All the respondents used tap water in their operation. The fact that C. coli was recovered from roast chicken suggested possible post-roast contamination and although the owner of the bar which C. coli was detected did not use same utensils for both raw and roasted meat, 38% (15/40) of nyama-choma bar operators reported using. The proportions of pubs using the same utensils for both raw and roast meat were not significantly different between those trained for hygiene (7/21, 33%) and not trained (8/19, 42%, x2=0.06, df=1, p=0.81), suggesting ineffectiveness of hygiene training provided by the health authorities. Future research should focus on updating the risk assessment and incentives of compliance to hygiene regulation.